Environmental preferences of brachiopods and bivalves across major climatic changes during the late Paleozoic ice age (Pennsylvanian, western Argentina) - Balseiro, Diego (2016)
During the late Palaeozoic ice age (LPIA), ice-proximal marine regional communities record contrastingresponses to climate change compared to ice-distal communities. However, there is still much to be understood in distalregions in order to fully understand the palaeobiological consequences of the LPIA. Here, were analyse brachiopod andbivalve environmental preferences along the bathymetric gradient during a major glacial event and the subsequent non-glacial interval in western Argentina. Median environmentalbreadths did not change with the reassembly of communitiesduring the non-glacial interval. Moreover, bivalves and brachiopod immigrants show similar environmental breadths although they tend to have immigrated from different palaeogeographical regions. These patterns reinforce the idea thatthe worldwide marine fauna was probably culled of stenotopic taxa during the LPIA. On the other hand, analysis of the preferred depths of survivors and immigrants sheds light on thesubstantial modification of the bathymetric diversity gradient.Among different possible explanations, the immigration oftaxa with affinities for deep environments is the only one supported. In addition, results underscore the observation thatthe higher turnover in the offshore environment was probablydriven by immigration rather than extinction. Finally, stabilityin environmental preferences at a regional scale is not mirrored by stability in survivors’ individual preferences, becausesurvivors’ preferred depth is not correlated during the glacialand non-glacial intervals. Moreover, the amount of change insurvivors preferred depth is not related to their environmentalbreadth, nor to their occupancy. These patterns suggest: (1)instability in realized niches; and (2) individual responses ofsurvivor genera